Fabrication of an anode-supported SOFC with a sol-gel coating method for a mixed-gas fuel cell - Vo, NXP; Yoon, SP; Nam, SW; Han, J; Lim, TH; Hong, SA (TRANS TECH PUBLICATIONS LTD, 2005)
An anode-supported type solid oxide fuel cell (SOFC) is a promising structure resulting in a very high performance because it consists of a very thin electrolyte. In the preliminary stage, we have succeeded in the fabrication of Samaria-Doped Ceria (SDC) thin film on a porous Ni-Al substrate using a sol-gel coating technique. The thin electrolyte film binds the substrate well and a single cell made with the SDC thin-film electrolyte and porous LSM cathode exhibited a good performance in a mixed-gas condition, even at intermediate temperatures. The single cell, consisting of 20 mum thin SDC electrolytes, the porous Ni-Al anode substrate, and a LSM cathode, exhibited an open circuit voltage of 0.82V and a maximum power density of 0.31 Wcm(-2) at 700degreesC with humidified methane and air mixtures. This cell also generated an open circuit voltage of about 1.1V and a maximum power density of 0.34 Wcm(-2) at 600degreesC with humidified hydrogen as the fuel and air as the oxidant.
Keywords: POLARIZATION; PERFORMANCE; ELECTRODE